Control of Botrytis cinerea Pers. in ‘Okitsu’ Satsuma mandarin by biological and chemical fungicides in Huaura, Peru - Cáceres Candia, Denis Paolo (2021)
The flowers blight caused by Botrytis cinerea Pers. is among the most important citrus diseases, especially in cultivars whose flowering coincides with the humid seasons of the year. As a result of the pathogenic features of this fungus and the complex nature of its control, it is necessary to establish a correct plan for the usage of highly efficient fungicides. The study aimed to evaluate the effect of four chemical fungicides, such as Captan (0.25%), Propineb (0.25%), Fludioxonil + Cyprodinil (0.05%), and Iprodione (0.15%); as well as the effect of a biological fungicide, such as Melaleuca alternifolia extract (0.1%), on Botrytis cinerea Pers. Two phases were established: the first, under laboratory conditions of Department of Plant Pathology of National Agrarian University-La Molina (UNALM), evaluated the effect on mycelial inhibition at 1, 3, and 7 days after inoculation with poisoned potato dextrose agar medium. The second, under field conditions (Sayan - Huaura), evaluated the effect on incidence of the disease in flowers. In the field condition, two applications, incidence, and humid chambers were evaluated. The yield was estimated by counting the fruits. The results showed that, under laboratory conditions, Captan, Fludioxonil + Cyprodinil, and Iprodione exhibited high efficacy in the control of B. cinerea. However, under field conditions, Fludioxonil + Cyprodinil and Iprodione exhibited a significant control of B. cinerea. A similar trend was obtained for the yield estimates.